2020
DOI: 10.1111/ejn.14777
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on dyskinesias

Abstract: Dopamine replacement therapy with L-DOPA remains the most widely prescribed treatment for Parkinson disease. However, prolonged treatment due to disease progression frequently causes unwanted motor movements known as levodopa-induced dyskinesias. Previous studies have established that alterations to the efferent circuitry of the striatum, a principal component of the basal ganglia, are in part responsible for the pathological motor consequences of prolonged levodopa treatment. While the role of the striatal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 140 publications
1
9
0
Order By: Relevance
“…This could suppress the ectopic release of L-DOPA-derived DA in the denervated striatum, as these channels are expressed on a multitude of cellular subtypes. 56 Both dopamine D1 and D2 receptors are implicated in dyskinesias, 57,58 but activation of D1-receptor containing MSNs (D1R-MSNs) is sufficient to induce dyskinetic behavior. 59,60 Indeed, in vivo photometry studies in genetically modified mice have shown transient increases in MSN activity that precede and predict (within 500 ms) the start of contraversive movements.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could suppress the ectopic release of L-DOPA-derived DA in the denervated striatum, as these channels are expressed on a multitude of cellular subtypes. 56 Both dopamine D1 and D2 receptors are implicated in dyskinesias, 57,58 but activation of D1-receptor containing MSNs (D1R-MSNs) is sufficient to induce dyskinetic behavior. 59,60 Indeed, in vivo photometry studies in genetically modified mice have shown transient increases in MSN activity that precede and predict (within 500 ms) the start of contraversive movements.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Both dopamine D1 and D2 receptors are implicated in dyskinesias, , but activation of D1-receptor containing MSNs (D1R-MSNs) is sufficient to induce dyskinetic behavior. , Indeed, in vivo photometry studies in genetically modified mice have shown transient increases in MSN activity that precede and predict (within 500 ms) the start of contraversive movements . Furthermore, a recent study in mice has used the targeted recombination in active population (TRAP) strategy to demonstrate that a specific subset of striatal cells (mostly direct pathway D1R-MSNs) is reliably activated with dyskinetic behavior associated with L-DOPA. , Optogenetic activation of these TRAP-ed cells elicited AIMs and contraversive rotations .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are other differences between MSNs in the direct and indirect pathways as well, aside from the dopaminergic receptors they express. In vitro studies have shown differences in resting membrane potential, excitability, threshold for action potential generation [ 273 ], and morphologic differences relating to the dendritic surface area [ 274 ].…”
Section: Mechanisms Of Neurodegeneration In Huntington’s Diseasementioning
confidence: 99%
“…Dopaminergic denervation and repeated L‐dopa treatment induce plastic changes involving both direct and indirect pathway SPNs. It remains unclear whether changes in the neuronal activity or morphology (dendritic spine pathology) of indirect pathway SPNs are associated with dyskinesia or are just a therapeutic effect of L‐dopa 49 . However, recent evidence suggests that functional changes within the indirect pathway may be also involved in LID.…”
Section: The Role Of Indirect Pathway Neuronsmentioning
confidence: 99%